2007
DOI: 10.1159/000104813
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among Kuwaiti Population Attending Primary Healthcare Setting: Prevalence and Influence of Sociodemographic Factors

Abstract: Objectives: The aim of this study was to estimate the prevalence of depressive disorders and the influence of sociodemographic characteristics on primary healthcare (PHC) setting in Kuwait. Subjects and Methods: A cross-sectional survey was conducted in PHC setting in Kuwait using the Beck Depression Inventory second edition questionnaire (BDI II) as a screening instrument, together with a sociodemographic questionnaire. A representative sample drawn from the target population consisted of 2,320 subjects of Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
5
23
2
Order By: Relevance
“…The rate was lower than that reported in Riyadh (18.8%) and Kuwait (20.5%) [12,13] and higher than in Qatar (13.5%, 2010). [14] Similar studies conducted in European countries revealed a prevalence rate ranging from 16.5% to 22.8%, [15][16][17] indicating that the rates in Gulf Region are comparable with those of Europe.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The rate was lower than that reported in Riyadh (18.8%) and Kuwait (20.5%) [12,13] and higher than in Qatar (13.5%, 2010). [14] Similar studies conducted in European countries revealed a prevalence rate ranging from 16.5% to 22.8%, [15][16][17] indicating that the rates in Gulf Region are comparable with those of Europe.…”
Section: Discussioncontrasting
confidence: 64%
“…[10,11] The scale consists of nine questions, for which the answers ranged from ''not at all'' (given a score of 0) to ''nearly every day'' (given a score of 3) experiencing the symptom within the last 2 weeks. The total score was calculated and categorized into no depression (0-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), and severe depression (15+). Weight and height were also measured for 836 participants (with a response rate of 98.4%), and body mass index (BMI) was calculated and categorized into underweight (less than 18.5 kg/m 2 ), normal weight (18.5-24.9), overweight (25-29.9), obesity (30-34.9), and severe obesity (more than 35 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Responses are summed to yield a total score that ranges from 0 to 63. The BDI-II has been used in previous studies of samples of students and primary health care attendees in the Arabian Gulf, including Kuwait [36,51,52], and an Arabic translation exists, produced by the method of back-translation. The internal consistency (Cronbach's alpha) for the 21 items, using the responses of all participants was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…The review of research evidence available indicates that the primary health-care clinician’s ability to detect depressive disorders is important to prevent suicide and reduce health-care cost because patients with depression visit health facilities frequently 5. However, the clinician’s ability to detect depression is sometimes affected by the presence of comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out so far in different countries of the world5,1826 have shown that symptoms of depression among medical patients were common and were associated with various factors. However, little is known about the prevalence of depression among medical patients.…”
Section: Introductionmentioning
confidence: 99%